Mauritania - Enhanced National Capacity in Telecommunications Sector Reforms - Govindan G. Nair (World Bank, Washington, DC, 2012)
Mauritania's 1998-2001 telecommunications reforms resemble many World Bank supported reform programs where overcoming capacity constraints can determine success in achieving development outcomes. Overcoming capacity constraints enabled this desert nation of over 2 million largely nomadic inhabitants to attain unanticipated levels of outcomes in three years of telecommunications reforms. New private investment of US$ 100 million in telecommunications was attracted over two years, equivalent to 10 percent of GDP; telephone line access multiplied twenty-fold; 6,000 new telecommunications-related jobs were created in the informal sector in the capital city (Noukachott) alone; and a multisector regulatory agency was established which is now regarded as a model in Africa. From lacking critical skills at the outset of these reforms, Mauritania became a source of lessons for neighboring countries on how to competitively tender utility licenses, effectively regulate utilities in a competitive setting, and privatize a telecommunications operator. Support for this capacity enhancement came from relatively modest external assistance with an estimated cost of slightly over one million dollars (World Bank Group staff time as well as consultancy support).